Identification of the long polar fimbriae gene variants in the locus of enterocyte effacement-negative Shiga toxin-producing Escherichia coli strains isolated from humans and cattle in Argentina - Galli, Lucía (2010)
The long polar fimbriae (Lpf) is one of few adhesive factors of Shiga toxin-producing Escherichia coli (STEC) and it is associated with colonization of the intestine. Studies have demonstrated the presence of lpf genes in several pathogenic E. coli strains, and classification of variants based on polymorphisms in the lpfA1 and lpfA2 genes has been adopted. Using a collection of Argentinean locus of enterocyte effacement (LEE)-negative STEC strains, we determined that the different lpfA types were present in a wide variety of serotypes with no apparent association between the types of lpfA1 or lpfA2 genes and the severity of human disease. The lpfA2-1 was the most prevalent variant identified, which was present in 95.8% of the isolates, and lpfA1-3 and lpfA2-2, proposed as specific biomarkers of E. coli O157:H7, were not found in any of the serotypes studied. The prevalence of lpf genes in a large number of strains is useful to understand the genetic diversity of LEE-negative STEC and to define the association of some of these isolates carrying specific lpf-variants with disease.